Reading faster - Nation, Paul (International Journal of English Studies, 2009)
This article describes the visual nature of the reading process as it relates to reading speed. It points out that there is a physical limit on normal reading speed and beyond this limit the reading process will be different from normal reading where almost every word is attended to. The article describes a range of activities for developing reading fluency, and suggests how the development of fluency can become part of a reading programme.